2002
DOI: 10.1097/00005373-200210000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial Complications of Preinjury Anticoagulation in Trauma Patients with Head Injury

Abstract: These data indicate that the trauma patient with preinjury anticoagulation such as warfarin or even aspirin who has an intracranial injury has a four- to fivefold higher risk of death than the nonanticoagulated patient. The efficacy of reversing the anticoagulant effect at the time of hospital admission remains to be evaluated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
101
0
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(112 citation statements)
references
References 7 publications
7
101
0
2
Order By: Relevance
“…Altogether, many TBI patients have multiple reasons for developing delayed hemorrhagic complications and ethanol levels may be another factor necessary to consider during management of TBI patients. Ethanol has been found to decrease collagen induced platelet aggregation and this may be a problem viewed in the light of the finding that patients on NSAIDs have a higher mortality rate after TBI [4,32]. In our study we also found a prolongation of CFT that may be interpreted as an impairment of the platelet activity.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Altogether, many TBI patients have multiple reasons for developing delayed hemorrhagic complications and ethanol levels may be another factor necessary to consider during management of TBI patients. Ethanol has been found to decrease collagen induced platelet aggregation and this may be a problem viewed in the light of the finding that patients on NSAIDs have a higher mortality rate after TBI [4,32]. In our study we also found a prolongation of CFT that may be interpreted as an impairment of the platelet activity.…”
Section: Discussionsupporting
confidence: 57%
“…It is also known that impairment of the coagulation of different origins, e.g. NSAID treatment or consumption coagulopathy, is associated with worse outcome in TBI patients [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…(21) These abnormalities in coagulation factors are closely associated with increased intake of anticoagulants, such as aspirin and warfarin, due to the recent increase in cardiovascular and cerebrovascular diseases, and patients who took such medicines increased the mortality rate four times compared to patients who did not take the medicines. (22) In this study, two patients who had a history of cerebral infarction and were taking aspirin and anticoagulants died after surgery. Of nine patients who had thrombocytopenia, seven died, revealing that thrombocytopenia itself has an adverse effect on the prognosis regardless of whether or not surgery is administered.…”
Section: Discussionmentioning
confidence: 91%
“…10 Franko et al also found a significant increase in mortality in patients that were anticoagulated, 23.9% versus controls, 4.9%. 19 Pieracci et al demonstrated increased risk of mortality in patients using warfarin before ICH compared with patients who did not.…”
Section: Warfarinmentioning
confidence: 90%